Respon Tanaman Kacang Hijau (Vigna radiata L.) terhadap Pemberian Pupuk Kandang Ayam dan Volume Penyiraman di Medium Sub Soil Inceptisol - Jusmi Sutrisna; Ardian Ardian; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The reseaerch intendeed to observe mung bean also their responded which proper treatment for growth and mung bean outcome. Its gave poultry manure and sprinkling volume on sub soil Inceptisol medium. The research held at experimental garden, placed at Faculty of Agriculture, Riau University, Bina Widya Kampus KM 12,5, Simpang Baru region, sub – district of Tampan, Pekanbaru. The research did during 3 months, starting on January to March 2017. The research had done experimental method which used a complete randomized factorial design that were consists of two factors; the first factor was poultry manure which consist of 4 stages were (0,40,60,80 g.polybag-1) for giving poultry manure. The second factor was sprinkling volume that consist of 3 stages were (500,1000,1500 ml. polybag-1) for sprinkling volume in the morning. The research observed parameters were plants height, number of branches, the age of the flower plants, the percentage of the effective root nodule, the percentage of planted pods per plant, and dry seed weight per plant. The result of the varience investigation has analyzed further by using Duncan’s multiple range test at 5% degree. Giving poultry manure 40 g.polybag-1 and 500 ml.polybag-1 in the morning on sub soil Inceptisol medium type can be increase growth and outcome of mung bean.Keywords: Mung bean, Poultry manure, Sprinkling volume, sub soil Inceptisol medium.